DIGITAL ENTREPRENEURIAL EMPOWERMENT AND MICROENTERPRISE SUCCESS: A REVIEW WITHIN THE CONTEXT OF KELANTAN, MALAYSIA - Abdullah , Zailani; Mamat , Salini Aina; Hasbolah , Hazrina; Tengku Anuar, Tengku Fauzan (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
In the rapidly evolving landscape of global business, the growth of small-scale ventures is increasingly dependent on the empowerment and inherent capabilities of the owner-manager. Despite rapid digitalisation, microenterprises in regional markets such as Kelantan continue to struggle with digital adoption. However, a significant theoretical and empirical gap exists regarding how localised socio-economic constraints influence the translation of digital tools into sustainable empowerment. This systematic literature review (SLR) addresses this gap by identifying the relationship between capabilities and the development of Digital Entrepreneurial Empowerment with a specific focus on the socio-economic context of microenterprises in Kelantan, Malaysia. The study examines the multifaceted dimensions of entrepreneurial empowerment, including innovation and technological capabilities. Through a review of existing systematic approaches, the study explores how this innovation and technological capabilities specifically translate into digital empowerment for micro-scale ventures in regional contexts. By employing the systematic approach, this study synthesises multifaceted dimensions of empowerment to explore how these factors collectively mitigate the unique challenges inherent in the Kelantan digital landscape. The review specifically seeks to rectify the lack of evidence-based insights regarding the digital divide in emerging regional markets. The findings not only contribute a localised framework to the academic discourse on digital entrepreneurship but also provide strategic implications for policymakers and business support entities to foster a more resilient, digitally inclusive microenterprise sector. Ultimately, this review serves as a strategic resource to bridge the gap between theoretical empowerment and the practical digital success of regional entrepreneurs.